Integrating Women's Rights and Climate Migrant Protection: Bridging Gaps in Vietnam - Ta, Khanh Linh; Linh, Pham Khanh (Serikat Pengajar Hak Asasi Manusia Indonesia, 2024)
Southeast Asia, a region at the forefront of the climate crisis, is experiencing a surge in climate-induced displacement, with projections indicating that 3.3 to 6.3 million internal displacements may occur in the lower Mekong sub-region by 2050. Climate migration in the Global South is not merely a matter of environmental survival but also a significant human rights concern—particularly for women. Female climate migrants are especially vulnerable to gender-based violence, trafficking, and restricted access to essential services such as sanitation, reproductive healthcare, and psychosocial support. Despite growing awareness, the intersectional vulnerabilities of these women remain insufficiently addressed in both academic literature and legal policy. While previous research has explored climate migration and women’s rights separately, few studies have engaged with their intersection—particularly within Global South contexts. This study seeks to bridge that gap by examining the identity, legal recognition, and lived experiences of female climate migrants, with Vietnam serving as a representative case study. The research employs a comparative legal analysis of international and Vietnamese legal frameworks, evaluating how existing laws conceptualise and safeguard female climate migrants. Methodologically, it draws on interdisciplinary literature and human rights-based approaches to interrogate both normative and practical gaps in protection. The findings reveal that prevailing legal regimes tend to classify women either as victims of climate disasters or as migrants, without adequately accounting for the convergence of these identities. This oversight contributes to fragmented protections and critical policy blind spots. In response, the study proposes a holistic framework that incorporates gender-responsive and climate-specific considerations into migration law and policy. By foregrounding the voices and rights of female climate migrants in the Global South, this research contributes to the advancement of human rights scholarship and advocates for inclusive, intersectional, and contextually grounded legal reforms. It highlights the urgent need for policies that not only address environmental displacement but also uphold the dignity and rights of the most affected.